2007
DOI: 10.1038/oby.2007.592
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific Difference in the Interconversion of Cortisol and Cortisone in Men and Women

Abstract: VIERHAPPER, HEINRICH, GEORG HEINZE, AND PETER NOWOTNY. Sex-specific difference in the interconversion of cortisol and cortisone in men and women. Obesity. 2007;15:820 -824. Objective: Our objective was to demonstrate that the smaller oxoreductase activity of 11␤-HSD1 in women would shift the interconversion of cortisol and cortisone toward cortisone, resulting in a larger amount of generated labeled cortisone in healthy women than in healthy men. Research Methods and Procedures:Using mass spectrometry, the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For example, recent research has shown sex differences in the activity of 11 b-hydroxysteroid dehydrogenase type 1 (Vierhapper et al 2007), an enzyme that reactivates glucocorticoids and modulates tissue exposure to glucocorticoid activity (Holmes and Seckl 2006). Therefore, cortisol concentration may not be the only factor determining the effects of HPAaxis reactivity on memory performance.…”
Section: Discussionmentioning
confidence: 96%
“…For example, recent research has shown sex differences in the activity of 11 b-hydroxysteroid dehydrogenase type 1 (Vierhapper et al 2007), an enzyme that reactivates glucocorticoids and modulates tissue exposure to glucocorticoid activity (Holmes and Seckl 2006). Therefore, cortisol concentration may not be the only factor determining the effects of HPAaxis reactivity on memory performance.…”
Section: Discussionmentioning
confidence: 96%
“…However, these ratios only reflect net balance between the activities of multiple enzymes and do not quantify rates of turnover between cortisol and cortisone. Others have administered labeled substrates for 11β-dehydrogenase, including 11α-[ 3 H]-cortisol (35), d4-cortisol (2), 11α-[ 2 H]-cortisol (36), and d2-cortisol (37), but the removal of these compounds is not exclusively dependent on 11β-dehydrogenase and R a of 11β-dehydrogenase product (labeled cortisone or liberated [ 3 H]) cannot be quantified accurately in steady state in the absence of simultaneous measurement of clearance of the product. Here, we used the gold standard approach, in which endogenous cortisone production is inferred from dilution of a “tracer” labeled cortisone, infused in steady state.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal life. During the postnatal period, there are few mechanisms to protect the offspring from excessive glucocorticoid exposure and HPA axis overactivation during the hyporesponsive period, which is a stage of resilience to mild stressors (42,74). This is a key event in the origin of long-term hypersensitivity to secondary stressors.…”
Section: R4mentioning
confidence: 99%